Pemanfaatan Fitur Trending Topic Twitter “X” sebagai Upaya Pemenuhan Kebutuhan Informasi Mahasiswa Program Studi Perpustakaan dan Ilmu Informasi Universitas Negeri Padang - Qalbina, Gita Syifa; Asmara, Rini (Lembaga Yasin AlSys, 2024)
This research is motivated by the phenomenon of widespread misuse of information spread on social media. Therefore, this study aims to describe how the utilization of Twitter's